Constitutions, courts, and history : historical narratives in constitutional adjudication - Uitz, Renáta (Central European University Press, 2005)
Emphasizes the role history and historical narratives play in constitutional adjudication. Uitz provocatively draws attention to the often-tense relationship between the constitution and historical precedence highlighting the interpretive and normative nature of the law. Her work seeks to understand the conditions under which references to the past, history and traditions are attractive to lawyers, even when they have the potential of perpetuating indeterminacy in constitutional reasoning. Uitz conclusively argues that this constitutional indeterminacy is obscured by 'judicial rhetorical toolkits' of continuity and reconciliation that allow the court's reliance on the past to be unaccounted for. Uitz' rigorous analysis and extensive research makes this work an asset to legal scholars and practitioners alike. The inquiry in this volume hopes to attract observers of constitutional adjudication, may they be reading constitutional jurisprudence from the quarters of constitutional law, constitutional history, political science or history departments.